WBG Electronics for Energy-Efficient Power Electronic Applications - Hildesson, Matilda; El Achkar, Lucia (My University, 2017)
An investigation between Wide Band Gap (WBG) transistors and silicon (Si) transistors were performed to investigate characteristics, materials, and best practice usage of different WBG transistors. The investigated WBG transistors were silicon carbide (SiC) and GaN transistors, but only GaN transistors were used as WBG transistors since the SiC transistors today are more applicable for high voltage applications. Two small compact dc/dc converters, with Si and gallium nitride (GaN) transistors respectively, were designed and constructed. The main purpose of the thesis was to investigate if WBG transistors had potential for future use in power electronic applications. The benefit of WBG transistors is that they can operate at higher switching frequencies and with lower switching losses compared to Si transistors. From the investigation of the WBG transistor it could be concluded that GaN transistors have a big potential. This is due to that GaN transistors can operate at higher switching frequencies and have smaller designs for almost the same efficiency as Si transistors.
Keywords: Elkraftteknik; Electric power engineering